De la psychanalyse au happening - Julio Premat (Mélanges de la Casa de Velázquez, 2008)
This article seeks to analyse certain aspects of the reception of Lacan’s theories by the Argentinian literary avant-garde in the nineteen-sixties. It highlights the shifts and deformations that accompanied this cultural transfer, which was more than simply geographical, recalling as it does the surrealist interpretations of another great name in psychoanalysis –Sigmund Freud– in the nineteen-twenties. The article commences by proposing a contextualisation of the figure of Oscar Masotta, Lacan’s introducer and translator but also a literary critic, creator and leading intellectual of the time. This is followed by an examination of the singular case of Osvaldo Lamborghini, one of his generation’s «accursed» writers, who impudently appropriated certain concepts and turns of phrase taken from Lacan. Such use could be classified as parodio (parody and hate) given the order of the transfer (in a psychoanalytical sense); but it could also be a driving force for writing, a canon for a non-canonical literature.